Working Capital Management and Leverage to Profitability: Case of Manufacturing Firms in Indonesia - Sany Sany; Andrew Winata; Teresa Veline Yasin (International Journal of Organizational Behavior and Policy, 2023)
This study aims to investigate whether Working Capital Management (WCM) and leverage affect firm profitability. Data concern was gathered from Bloomberg database terminal. Sample is manufacturing companies listed in Indonesian Stock Exchange (IDX) over the period of 2014 – 2020, which already established for some time. WCM is measured by using Cash Conversion Cycle (CCC), profitability is proxied with ROA while leverage is proxied by Debt-to-Equity. We find that the length of CCC days does not affect profitability, while the higher proportion of debt to equity will reduce profitability, on the other hand, the higher sales growth will enhance better firms’ profitability performance. Our findings contribute to understanding of the relationship of CCC and leverage on profitability in emerging markets.